Exploring the relation between farmer organization and welfare using propensity score matching approach: Evidence from madurese traditional salt farmers in indonesia - Prihantini, Campina Illa; AR, Nuhfil Hanani; Syafrial; Asmara, Rosihan (Asian Journal of Agriculture and Rural Development, 2024)
This research aims to examine the relation between farmer organization and welfare using Propensity Score Matching approach. Numerous prior studies have demonstrated that farmers’ involvement in a producer group significantly affects their income levels, efficiency rates, and the adoption of cutting-edge agricultural technologies. However, there have been few studies on salt farming in Madura Island, despite its status as a primary salt producer in Indonesia. This study focused on examining how the participation of salt farmers in farmer groups, specifically known as the “Traditional Salt Business Group” (or Kelompok Usaha Garam Rakyat [KUGAR] in Indonesian), impacts their agricultural income. In this study, the researchers examined primary data collected through interviews with 115 traditional salt farmers on Madura Island, East Java, Indonesia. Logistic regression analysis revealed three independent variables affecting the decisions of salt farmers, specifically farmer’s latest level of education, salt production in the last season, and the number of their family members. Then, employing a Propensity Score Matching (PSM) approach, the study showed a significant income disparity between salt farmers who were KUGAR members and those who are not. Moreover, the level of education emerged as a key determinant influencing salt farmers’ decisions to join KUGAR. Furthermore, the Indonesian government could intervene by encouraging younger salt farmers to join the producer groups to realize benefits, including improvements in the well-being of salt farmers.